Weakly bound halo breakup of neutron-Li-7 and nucleon-Be-7 on a lead target - Mukeru, B.; Frederico, T.; Tomio, Lauro [UNESP] (Amer Physical Soc, 2020)
A comparative analysis of the breakup cross-sections, using continuum discretized coupled-channel approach, is presented for the weakly bound p-wave neutron Li-7 and nucleon-Be-7 projectiles on the Pb-208 target, by investigating the role of interaction effects between the core (Li-7, Be-7) with the target. The extra charge in the B-8 has the effect to increase the Coulomb contribution in the breakup reaction channel. By fixing both projectile ground-state binding energies at 0.137 MeV (B-8 experimental one), with incident energies at the Coulomb barrier and above, we found that the charge difference accounts for over 30% of the neutron-Be-7 breakup cross sections, substantially larger than the corresponding one for proton-Be-7. The large enhancement of the neutron-halo breakup cross-section with respect to the proton-halo case shown in this work is associated to dynamical effects coming from the excitation of the projectile internal continuum due to the nucleon-target and core-target interactions, together with the widely accepted static effects coming from the long wave-function tail of the weakly bound neutron. The interplay between these dynamical and static effects in the energy spectrum of the B-8 fragments is visible, revealed by the peak of the energy distribution pushed to higher relative energies. This follows from the two-body final state interactions between the charged fragments distorted by the three-body reaction environment.